Green Synthesis of Gold Nanoparticles Using Tamarindus indica Extract as a Bioreductant - Gourav, Pradyumn; H. Hasan, Syed (Innovations in Corrosion and Materials Science (Discontinued), 2015)
Over the last few decades, economically viable, straightforward and green route for the synthesis of nanomaterial has drawn the attention of researchers in the area of nanoscience and technology. Applications of economical and non-toxic chemicals, environmentally safer solvents and renewable products materials are the advantages of nanoscience and technology considering researchers to use green route for large scale manufacturing. It is well documented that the synthesis and stabilization of nanomaterials usually depends upon reaction medium, reducing agents (RA) and capping agent, that is why these three factors must be taken into the consideration comprehensively from an economic and green chemistry perspective. A novel green approach for the synthesis of gold nanoparticles has been proposed over here by using fruit extract of Tamarindus indica fruit extract (TIFE). When 2 mL of TIFE was added into 2 mL of 1 mM tetrachloroauric acid solution the color changed from light yellow to purple brown was observed indicating the formation of Gold nanoparticles. It was confirmed by UV-Visible spectroscopy showing a sharp peak at 540 nm. Transmission Electron Microscopy (TEM) an EDAX analyses indicated that the shapes and sizes of formed gold nanoparticles were depending upon the reaction conditions. X-Ray diffraction pattern indicated that the synthesized nanoparticles were purely face centered cubic crystal. The gold nanoparticles were found to have significant in vitro stability. The mechanism of formation of gold nanoparticles has been explored and it was found that tartaric acid and glucose which were the major active constituents of the TIFE, were behaving as a bioreductants as well as capping agents.
Keywords: Bioreductant